Influence of the covering depth and the seed frаction on the content of starch in corn grain and bioethanol output - Паламарчук, В. Д. (Scientific Progress & Innovations, 2018)
The article presents the results of research conducted during 2014–2016 on the experimental field of the Plant Growing, Selection and Bioenergetic Cultures Department of the State Enterprise «Kordelivs’ka», IC of the National Academy of Sciences of Ukraine on the influence of the covering depth and the size of the seed fraction on the productivity, content and output of starch, the approximate output of bioethanol in hybrids of corn. The yield, starch content and bioethanol output from the studied corn grains hybrids were determined by a group of ripeness, genetic features and elements of agrotechnics, such as the seed fraction and the its covering depth. Lengthening of the growing season provided the growth of the studied indicators. The productivity of plants of studied corn hybrids, on average over three years of research, is 9,128 tons/ha, at sowing to a depth of 7 cm – 9,093 tons/ha, and at sowing to a depth of 11 cm – 8,961 tons/ha. The use of non-deep covering of seeds (4 cm) contributed the bioethanol output in the range of 3,23–4,11 thousand liters/ha, the middle (7 cm) – 3,21–4,23 thousand liters/ha and deep (11 cm) – 3,11–4,17 thousand liters/ha. The use of the large and middle fraction of seeds influences positively on the increase in yield, starch and the bioethanol output from grain in comparison with the small fraction of seeds.